A BIM-based framework for construction project scheduling risk management. (17th January 2020) - Abanda, F.H.; Musa, A.M.; Clermont, P.; Tah, J.H.M.; Oti, A.H.
The management of risks has been at the heart of most construction projects. Building information modelling (BIM) provides opportunities to manage risks in construction projects. However, studies about the use of BIM in risk management are sketchy with a lack of a systematic approach in using BIM for managing risk in construction projects. Based on existing risk models, this study investigated and developed a BIM-based framework for the management of construction project scheduling risk. Although, the frameworks were developed by mining risk management processes from Synchro and Vico, both being amongst leading 4D/5D BIM software systems, they can inform risk management in BIM projects that are supported by 4D/5D BIM software systems that contain risk management modules. The frameworks were validated for their syntactic and semantic correctness.